Nearest neighbour distance does not affect escape behaviour in urban hooded crows - Novčić, Ivana; Mikula, Peter (Behavioural processes, 2024)
The nearest-neighbour distance is an important property of a group, as individuals can obtain environmental information more quickly and easily from nearby individuals. We examined whether distance to the nearest neighbour affected two components of escape behaviour - alert distance (AD) and flight initiation distance (FID) - in an urban population of hooded crows Corvus cornix, while controlling for confounding variables. We did not find evidence that AD and FID were influenced by the nearest neighbour distance. However, both AD and FID were negatively affected by feeding activity of individuals - focal crows alerted later and escaped at shorter distance if they were feeding during our approach. In addition, AD and FID were positively related to starting distance and grass coverage. The lack of evidence for the nearest neighbour effect on escape behaviour of crows may be due to: (1) disturbance by close neighbours that may impede antipredator behaviour of focal birds, (2) variable distribution of familiar, dominant or experienced individuals within a flock, and (3) dynamic change in position of the nearest neighbour during the potential predator approach.
Keywords: vrány; Behavior, Animal; Feeding Behavior; úniková reakce; mužské pohlaví; ženské pohlaví; zvířata; Escape Reaction; Female; Male; stravovací zvyklosti; Crows; chování zvířat; Animals